What is the Appropriate Nodular Diameter in Thyroid Cancer for Extraction by Transoral Endoscopic Thyroidectomy Vestibular Approach Without Breaking the Specimens? A Surgicopathologic Study. Issue 6 (December 2018) - Wu, Yi-Ju; Chi, Shun-Yu; Elsarawy, Ahmed; Chan, Yi-Chia; Chou, Fong-Fu; Lin, Yu-Cheng; Wee, Sin-Yong; Pan, Cheng-Chung; Cheng, Ben-Chung; Lin, Chih-Che
Abstract : Transoral Endoscopic Thyroidectomy Vestibular Approach (TOETVA) is a novel technique with better cosmetic results. However, extraction of a large malignant thyroid nodule from the central incision of TOETVA necessitates breaking it into pieces to avoid mental nerve injury, a situation that may violate a proper oncological surgery. In this study, we sought the appropriate nodular diameter in thyroid cancer to be removed in an intact status through the central incision of the TOETVA technique. A total of 27 cases of thyroid nodules were operated using the TOETVA technique from Aug 2016 to July 2017. Excluding 10 benign goiters, the specimens of 17 thyroid cancer cases were divided into intact (group T, n=7) and fragmented (group F, n=10), with a median nodular diameter of 18.35 and 30.30 mm, respectively. Receiver operating characteristic (ROC) curve analysis revealed that the safest nodular diameter is 20 mm, with 100% sensitivity and 87.5% specificity.